AB1041 BIOLOGICS IN ADULT'S ONSET STILL'S DISEASE: TREATMENT STRATEGIES AND SAFETY IN SINGLE CENTER COHORT WITH LONG-TERM FOLLOW-UP. (2nd June 2020) - Kougkas, N.; Avgustidis, N.; Pitsigavdaki, S.; Pateromichelaki, K.; Repa, A.; Molla Ismail Sali, A.; Eskitzis, A.; Bertsias, G.
Abstract : Background: Adult-onset Still's disease (AOSD) is a rare systemic inflammatory disorder. In recent years biological disease modifying antirheumatic drugs (bDMARDs) are becoming increasingly important for its treatment. Objectives: To evaluate disease outcomes, treatment strategies and their long-term safety in a cohort of AOSD patients treated with bDMARDs. Methods: A single-center retrospective study of patients diagnosed with AOSD until 2019 was conducted. Patients were included if they: a) were 16 years old or older, b) met the Yamaguchi criteria and c) had received a bDMARD Demographics, clinical and laboratory parameters were collected at the time of diagnosis. Data regarding treatment lines included: the previous and concomitant conventional disease modifying antirheumatic drugs (cDMARDs), the type of initial bDMARD, switches, survival and corticosteroids discontinuation. Adverse events related to treatment and disease outcomes including death and amyloidosis were also recorded. Results: Sixteen patients with AOSD (Table 1 ) refractory to cDMARDs were administered biologics. The median duration of follow-up was 14 years (range 1-24). Consistent with recent literature 1, two distinct disease patterns were recognized: the systemic form (SF) and the chronic articular form (CAF). In the SF the leading clinical symptoms were fever, pericarditis and pleuritis. In CAF the leading clinical symptom was persistent RA-like arthritis. Patients with the SF were treated with anakinra (n=4), tocilizumab (TCZ; n=3), canakinumab (n=1) and anti-TNFa (1 adalimumab, 1 etanercept) (n=2). Patients with the CAF received anti-TNFa (3 infliximab, 1 etanercept) (n=4) and TCZ (n=2). The median time from biologic initiation to corticosteroids discontinuation was 6.5 months, (range 2-32), (Table 2 ). 9 patients (56.25%) remained on treatment with the initial bDMARD, 4 patients (25%) received treatment with two and 3 patients (18.75%) with ≥ 3 bDMARDs. All patients with the CAF were on bDMARD at the end of follow-up, while 4/10 patients (40%) with the SF discontinued it. During follow-up only one serious adverse event was attributed to bDMARD (allergic reaction to infliximab infusion). There were no cases of amyloidosis or deaths Conclusion: Dichotomous phenotype in AOSD can determine treatment strategy for initial biologic treatment. Inhibition of IL-1 and IL-6 was the preferred therapeutic option for systemic form while inhibition of TNF and IL-6 was the preferred option for the chronic articular form. All of the above bDMARDs have favorable long-term safety profile in patients with AOSD. References: [1]François Vercruysse et al. Adult-onset Still's disease biological treatment strategy may depend on the phenotypic dichotomy Arthritis Research & Therapy. 2019 Disclosure of Interests: Nikolaos Kougkas: None declared, Nestor Avgustidis: None declared, Sofia Pitsigavdaki: None declared, Katerina Pateromichelaki: None declared, ARGYRO REPA: None declared, Ainour Molla Ismail Sali: None declared, Anastasios Eskitzis: None declared, George Bertsias Grant/research support from: GSK, Consultant of: Novartis